Peningkatan Kompetensi Guru dalam Membuat dan Memanfaatkan Alat Peraga Sederhana sebagai Display Kelas bagi Guru SD Negeri Telaga Baru Tahun Pelajaran 2020/2021 - Jawariah (Jurnal LENTERA: Jurnal Studi Pendidikan, 2021)
The use of simple teaching aids is one way to hone teacher competence in the teaching and learning process. For this reason, this research was conducted to improve the competence of teachers in their respective fields which was carried out at SD Negeri Telaga Baru, Taliwang District. The creation of props is also used as a class display. This manifests two advantages in terms of 1) teacher improvement in making, utilizing, and designing teaching aids, 2) creating fun classroom displays for students. The research was conducted in two cycles. The stages of the activity are 1) Socialization, 2) KD analysis and types of teaching aids, 3) Determining the sketch/pattern of teaching aids, 4) Making props that have been determined, 5) Presentation on the props that have been made, 6) Socialization about the second cycle, as a follow-up to the improvement of the first cycle, and 7) Exhibition of works/work titles. In the results of the first cycle, the teacher improved the components used from the teaching aids, in the second cycle the teacher carried out the working title because he had realized the teaching aids that were in line with expectations. This certainly manifests the results of a significant increase in teacher competence because they have carried out cognitive and technical processes in making works in the form of teaching aids